2019
DOI: 10.17576/pengurusan-2019-56-09
|View full text |Cite
|
Sign up to set email alerts
|

Practicing and Factors Infuencing the Effective Implementation of Strategic Information Systems Planning in Public Agency

Abstract: Strategic Information Systems Planning (SISP) guided organization in achieving its target. The importance of SISP increases proportionately with the uncertainty of business requirements. Failures in implementing SISP may affect organizational service delivery and reputation. This paper discusses on the evaluation of the practice and influencing factors of SISP implementation in a public sector. The Human Organization Technology-fit framework was used to evaluate the effectiveness of SISP from human, organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Moreover, significant commitment is expected on the part of top management to ensure the existence of internal resources (financial allocations) to deliver IS services. Whereas Boateng (2020) found budget constraint as a major inhibitor to SISP success in developing nations, there is however the need to forecast IT resource requirements and to allocate needed IT resources for IS project success (Angsor and Yusof, 2019). Thus, significant commitment is required to ensure that there exist internal resources (financial allocations) to support IS services.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, significant commitment is expected on the part of top management to ensure the existence of internal resources (financial allocations) to deliver IS services. Whereas Boateng (2020) found budget constraint as a major inhibitor to SISP success in developing nations, there is however the need to forecast IT resource requirements and to allocate needed IT resources for IS project success (Angsor and Yusof, 2019). Thus, significant commitment is required to ensure that there exist internal resources (financial allocations) to support IS services.…”
Section: Discussionmentioning
confidence: 99%
“…The finding revealed that among the CSFs enabling the use of SISP is the top management involvement. Moreover, knowledge Critical success factors of SISP and expertise; stakeholder engagement; governance and top management support; financial allocation; and infrastructure capabilities are the major factors for the effective implementation of SISP (Angsor and Yusof, 2019).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Our focus on this article is on the 4th to 6th steps in the process of clearance of Customs goods, namely on the aspect of processing digital K1 forms via the CIS platform until it is approved and the good is released. It is expected that there are weaknesses in the management flow due to lack of knowledge and skills among officials, or breach of Integrity in the process of handling K1 forms especially related to the pledging of vehicle tariff code (i.e., vehicle type, use of class, and cubic capacity) and the determination of Customs value or CIF (Cost, Insurance, Freight) based on the gazetted price (Ismail, 2019;Angsor & Yusof, 2019). Following the Customs Duty Order (2017), Excise Duty Order (2017) and Goods and Services Tax Order (2014), the determination of Customs value (i.e., CIF) is an important key for deciding tax and excise duties rate, thus requires information of vehicle chassis number, year of manufacture and date of first registration in the origin country.…”
Section: Research Problemmentioning
confidence: 99%